2020
DOI: 10.1371/journal.pone.0235430
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial metabolic genes provide phylogeographic relationships of global collections of Aedes aegypti (Diptera: Culicidae)

Abstract: Phylogeographic relationships among global collections of the mosquito Aedes aegypti were evaluated using the mitochondrial Cytochrome C Oxidase 1 (CO1) and NADH dehydrogenase subunit 4 (ND4) genes including new sequences from Sri Lanka. Phylogeographic analysis estimated that Ae. aegypti arose as a species~614 thousand years ago (kya) in the late Pleistocene. At 545 kya an "early" East African clade arose that continued to differentiate in East Africa, and eventually gave rise to three lineages one of which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…In this inference, an alternative scenario for direct dispersal from East Africa to Asia (Figure 2, blue arrow) was not supported statistically, despite geographic proximity. However, this East African route to Asia either directly across the Indian Ocean or via the Arabian Peninsula was once proposed [115]; and in a more recent report, this route of dispersal is inferred to have occurred by the ancestral species more than once in geologic period [120]. Although the conclusion of the latter report is interesting, it cannot be directly applied to the discussion of the dispersal of this mosquito spanning only the past several centuries because the mosquitoes in the geologic times were probably not identical to the extant Ae.…”
Section: Routes and Directions Of Aedes Aegypti Dispersal To Asiamentioning
confidence: 99%
“…In this inference, an alternative scenario for direct dispersal from East Africa to Asia (Figure 2, blue arrow) was not supported statistically, despite geographic proximity. However, this East African route to Asia either directly across the Indian Ocean or via the Arabian Peninsula was once proposed [115]; and in a more recent report, this route of dispersal is inferred to have occurred by the ancestral species more than once in geologic period [120]. Although the conclusion of the latter report is interesting, it cannot be directly applied to the discussion of the dispersal of this mosquito spanning only the past several centuries because the mosquitoes in the geologic times were probably not identical to the extant Ae.…”
Section: Routes and Directions Of Aedes Aegypti Dispersal To Asiamentioning
confidence: 99%
“…single focal expansion). When Badulla is considered, this invasion should be quite recent, as the genetic diversity of the Badulla population (=0.002) is approximately six fold lower than the genetic diversity reported for Senegal (=0.0119) (Fernando et al, 2020). According to Tabachnick and Powell (1979), after a founder event, a minimum of 10 5 generations is needed prior to restoring the heterozygosity to the level of original population.…”
Section: Discussionmentioning
confidence: 99%
“…When all the samples of the current study were analyzed together with the 40 selected Sri Lankan samples that were analyzed by Fernando et al (2020), two distinct clades were revealed (bootstrap support = 100%): one clade consisting of samples from Trincomalee (N=11; 5 from current study). Sri Lankan Journal of Biology 7(2)…”
Section: Phylogenetic Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…Mitochondrial genes, such as COI, are widely used to understand vector insect populations and their molecular, genetic evolution, dispersal patterns, phylogeny, and population dynamics [ 11 , 12 ]. These conserved genes present high levels of polymorphism and divergence among species, making them good molecular markers [ 13 , 14 ] that can help describe pest populations to carry out adequate entomological monitoring [ 15 ] and implement better control practices.…”
Section: Introductionmentioning
confidence: 99%